IT tools in the virtualization of the software implementation and maintenance process - Chomiak-Orsa, Iwona; Gryncewicz, Wiesława; Leszczyńska, Maja (Narzędzia informatyczne wykorzystywane w procesie wirtualizacji wdrażania i utrzymania oprogramowania, 2012)
By implementing modern technological solutions, companies re-organize their activities. The remote software implementation process and then the remote maintenance mean for companies a new approach to gaining competitive advantage. In practice, it gives the opportunity to reduce costs and hence the prices of services. These two processes become also independent of the geographical location of the client and the contractor, which can significantly reduce response time to reported problems and help ensure the higher quality of service. The IT support is needed to efficiently and quickly virtualize software implementation and maintenance process, so the aim of this paper is to present and characterize such IT tools
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 1 (23), s. 9-20
Keywords: virtualization; implementation; maintenance process; wirtualizacja; wdrażanie IT; utrzymanie oprogramowania